EVALUATION OF THE IMPLEMENTATION OF RABIES-TRANSMITTING ANIMAL BITES SURVEILLANCE AT ALAK HEALTH CENTER - Wahyuni, Maria Magdalena Dwi; Weraman, Pius; Nadut, Valentinus Aldino; Sogen, Yosep Ledung; Lumenta, Febyola Giovanni; Wolla, Marliance Lewo; Amas, Gloria Andra Umbu (JURNAL WIDYA MEDIKA, 2025)
Animal bites that transmit rabies are zoonotic diseases and remain a public health problem in Indonesia, including in East Nusa Tenggara, which has experienced an extraordinary event (KLB). Since 2023, the Alak Health Center has routinely conducted rabies monitoring due to the significant increase in cases every year and the high risk of death if left untreated. Therefore, a structured monitoring system is essential for rabies prevention and control. This study aims to describe the implementation of the rabies monitoring system at the Alak Health Center using a systems approach. A qualitative descriptive design was used, involving three monitoring officers as respondents. Data collection was carried out using questionnaires and mobile phones for documentation. The results showed that the input variables—materials, funds, and markets—were well met, but human resources were still inadequate because officers were assigned various monitoring responsibilities. In terms of process, epidemiological investigations and medical management have been carried out 100%. Outputs are met through routine reporting to the Kupang City Health Office. However, the expected results have not been achieved due to limited public awareness and participation in monitoring the movement of wild animals. The impact variable was achieved, as none of the 22 cases reported in weeks 1–19 of 2025 developed into suspected rabies cases. This demonstrates the effectiveness of monitoring in preventing rabies cases. However, ongoing challenges include excessive workload for monitoring officers and inadequate community engagement, highlighting areas for improvement in the sustainability of rabies control efforts.